No Influence of Dabigatran Anticoagulation on Hemorrhagic Transformation in an Experimental Model of Ischemic Stroke - Bohmann, Ferdinand (Public Library of Science, 2012)
BACKGROUND: Dabigatran etexilate (DE) is a new oral direct thrombin inhibitor. Clinical trials point towards a favourable risk-to-benefit profile of DE compared to warfarin. In this study, we evaluated whether hemorrhagic transformation (HT) occurs after experimental stroke under DE treatment as we have shown for warfarin. METHODS: 44 male C57BL/6 mice were pretreated orally with 37.5 mg/kg DE, 75 mg/kg DE or saline and diluted thrombin time (dTT) and DE plasma concentrations were monitored. Ischemic stroke was induced by transient middle cerebral artery occlusion (tMCAO) for 1 h or 3 h. We assessed functional outcome and HT blood volume 24 h and 72 h after tMCAO. RESULTS: After 1 h tMCAO, HT blood volume did not differ significantly between mice pretreated with DE 37.5 mg/kg and controls (1.5±0.5 µl vs. 1.8±0.5 µl, p>0.05). After 3 h tMCAO, DE-anticoagulated mice did also not show an increase in HT, neither at the dose of 37.5 mg/kg equivalent to anticoagulant treatment in the therapeutic range (1.3±0.9 µl vs. control 2.3±0.5 µl, p>0.05) nor at 75 mg/kg, clearly representing supratherapeutic anticoagulation (1.8±0.8 µl, p>0.05). Furthermore, no significant increase in HT under continued anticoagulation with DE 75 mg/kg could be found at 72 h after tMCAO for 1 h (1.7±0.9 µl vs. control 1.6±0.4 µl, p>0.05). CONCLUSION: Our experimental data suggest that DE does not significantly increase hemorrhagic transformation after transient focal cerebral ischemia in mice. From a translational viewpoint, this indicates that a continuation of DE anticoagulation in case of an ischemic stroke might be safe, but clearly, clinical data on this question are warranted.